2018
DOI: 10.1186/s12870-018-1403-5
|View full text |Cite
|
Sign up to set email alerts
|

ChIP-Seq reveals that QsMYB1 directly targets genes involved in lignin and suberin biosynthesis pathways in cork oak (Quercus suber)

Abstract: BackgroundGene activity is largely controlled by transcriptional regulation through the action of transcription factors and other regulators. QsMYB1 is a member of the R2R3-MYB transcription factor family related to secondary growth, and in particular, with the cork development process. In order to identify the putative gene targets of QsMYB1 across the cork oak genome we developed a ChIP-Seq strategy.ResultsResults provide direct evidence that QsMY1B targets genes encoding for enzymes involved in the lignin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 115 publications
3
31
0
Order By: Relevance
“…Based on data validated in the model plant A. thaliana , we used a computational approach to identify cis -regulatory elements whose putative trans-acting factors might play a role in C 4 compartmentalization. These data have been used to investigate the putative role of orthologous genes in other crops ( Capote et al, 2018 ; Moon et al, 2018 ; Burgess et al, 2019 ; Zeng et al, 2019 ; DeMers et al, 2020 ; Elzanati et al, 2020 ; Gray et al, 2020 ; Zhou et al, 2020 ), and allow us to generate a compelling hypothesis, as it is expected that similar DNA-binding domains of trans-acting factors would have similar DNA sequence preferences ( Lambert et al, 2019 ). However, several complementary experimental approaches will be needed to provide evidence of functional significance in C 4 plants.…”
Section: Discussionmentioning
confidence: 99%
“…Based on data validated in the model plant A. thaliana , we used a computational approach to identify cis -regulatory elements whose putative trans-acting factors might play a role in C 4 compartmentalization. These data have been used to investigate the putative role of orthologous genes in other crops ( Capote et al, 2018 ; Moon et al, 2018 ; Burgess et al, 2019 ; Zeng et al, 2019 ; DeMers et al, 2020 ; Elzanati et al, 2020 ; Gray et al, 2020 ; Zhou et al, 2020 ), and allow us to generate a compelling hypothesis, as it is expected that similar DNA-binding domains of trans-acting factors would have similar DNA sequence preferences ( Lambert et al, 2019 ). However, several complementary experimental approaches will be needed to provide evidence of functional significance in C 4 plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous transcriptomic analyses identifying the putative downstream targets of some MYB transcription factors demonstrate that they do not solely control aliphatic suberin biosynthesis and deposition. Additionally, these transcription factors also regulate the expression of several genes involved in the phenylpropanoid and cell wall metabolism pathways, suggesting that they have a global role in the formation of suberin lamellae (Capote et al, 2018;Lashbrooke et al, 2016;Legay et al, 2017). Their role as master regulators is further supported by the recent discovery that AtMYB92 upregulated the expression of several glycolytic and fatty acid biosynthetic genes, i.e.…”
Section: Multiple Transcription Factors Fine Tuning Suberin Depositionmentioning
confidence: 93%
“…The induction of suberization by abscisic acid was reported decades ago (Cottle & Kolattukudy, 1982), while its repression by ethylene was recently suggested (Barberon et al, 2016). The direct activation of several suberin-biosynthesis genes by MYB transcription factors has been reported for QsMYB1, AtMYB39, AtMYB92, and AtMYB107 (Capote et al, 2018;Cohen et al, 2020;Gou et al, 2017;To et al, 2020). Recently in kiwifruits, Wei and coworkers showed that abscisic acid induced the expression of AchnMYB41 which upregulated downstream suberin-related genes .…”
Section: Multiple Transcription Factors Fine Tuning Suberin Depositionmentioning
confidence: 97%
See 1 more Smart Citation
“…This species has been implemented in reforestation strategies (Costa et al 2017; Duque-Lazo et al 2018), and it is a significant asset in agro-silvopastoral practices (Bugalho et al 2012). The cork is a high-value-added resource for the industry (Capote et al 2018; Testillano et al 2018). Additionally, cork oak acorns are a supply of nutrient-rich food for wildlife, livestock and some human populations (Bugalho et al 2012; Pausas et al 2012).…”
Section: Introductionmentioning
confidence: 99%